CHANGES OF APELIN-13 AND CYSTATIN C LEVELS AND METABOLIC PROFILE IN PATIENTS WITH HYPERTENSION AND FREQUENT VENTRICULAR EXTRASYSTOLE - Kuzminova, N.V.; Ivankova, A.V.; Lozinsky, S.E.; Knyazkova, I.I.; Gavrylyuk, A.O.; Shkarivskyi, Yu.L.; Kulchytska, O.M. (World of Medicine and Biology, 2022)
We examined 82 patients with stage II hypertension. 50 of them had frequent ventricular arrhythmias according to Holter electrocardiogram monitoring. 32 patients had verified stage II hypertension without any heart rhythm disorders, another 30 healthy individuals were included in the control group. It was found that in patients with ventricular arrhythmias, the level of apelin-13 was significantly (p
Keywords: apelin-13; cystatin C; glomerular filtration rate; metabolic cardiovascular risk factors